Nuclear Compartmentalization Contributes to Stage-Specific Gene Expression Control in Trypanosoma cruzi - Pastro, Lucía; Smircich, Pablo; Di Paolo, Andrés; Becco, Lorena; Duhagon, María A.; Sotelo-Silveira, José; Garat, Beatriz (Frontiers in Cell and Developmental Biology, 2017)
In the protozoan parasite Trypanosoma cruzi, as in other trypanosomatids, transcription of protein coding genes occurs in a constitutive fashion, producing large polycistronic transcription units. These units are composed of non-functionally related genes which are pervasively processed to yield each mRNA. Therefore, post-transcriptional processes are crucial to regulate gene expression. Considering that nuclear compartmentalization could contribute to gene expression regulation, we comparatively studied the nuclear, cytoplasmic and whole cell transcriptomes of the non-infective epimastigote stage of T. cruzi, using RNA-Seq. We found that the cytoplasmic transcriptome tightly correlates with the whole cell transcriptome and both equally correlate with the proteome. Nonetheless, 1,200 transcripts showed differential abundance between the nuclear and cytoplasmic fractions. For the genes with transcript content augmented in the nucleus, significant structural and compositional differences were found. The analysis of the reported epimastigote translatome and proteome, revealed scarce ribosome footprints and encoded proteins for them. Ontology analyses unveiled that many of these genes are distinctive of other parasite life-cycle stages. Finally, the relocalization of transcript abundance in the metacyclic trypomastigote infective stage was confirmed for specific genes. While gene expression is strongly dependent on transcript steady-state level, we here highlight the importance of the distribution of transcripts abundance between compartments in T. cruzi. Particularly, we show that nuclear compartmentation is playing an active role in the developmental stage determination preventing off-stage expression.